EXTERN CRITICISM OF HADITH THOIFAH MANSHURAH IN THE BOOK OF SHAHIH IBNU HIBBAN - Ali Mahfuz Munawar (IAINU Kebumen Prodi IAT, 2026)
The term Thaifah Manshurah (the victorious group) has been adopted by certain extremist violent groups. Previously, since the 1980s, they more commonly referred to themselves as mujahidin (those who engage in jihad). The issue of contradictions among various hadith has long been a subject of discussion in hadith studies, especially in the context of confronting enemies of Islam who attempt to fabricate hadith with the aim of dividing the Muslim community. Therefore, it is crucial to understand the authenticity and classification of hadith, particularly in educational contexts. The addition of this designation is intended to motivate and sustain a spirit of struggle. They claim to be the group foretold to always prevail in struggle and combat, as mentioned in the saying of the Prophet Muhammad (peace be upon him): “Thaifah Manshurah is the victorious group.” However, hadith scholars differ in their interpretations regarding who exactly constitutes this victorious group. In reality, the term Thaifah Manshurah does not only refer to those engaged in warfare, but also encompasses individuals who consistently uphold righteousness and virtue. This study is a library research employing the method of takhrij al-hadith. The object of this research is the hadith found in Sahih Ibn Hibban, narrated by Muhammad ibn Hibban al-Busti, concerning Thaifah Manshurah, understood as the victorious or striving group. The findings of this study indicate that the hadith is muttashil (having an unbroken chain) reaching back to the Prophet Muhammad (peace be upon him). Its narrators are regarded as ‘adl (upright) and dhabit (precise in transmission), and its matn (text) falls into the category of ghayr shadh (non-anomalous) and ghayr ‘illah (free from hidden defects).